A review: Hybrid locomotion of in-pipe inspection robot - Roslin N.S.; Anuar A.; Jalal M.F.A.; Sahari K.S.M. (Elsevier Ltd, 2023)
In the past five years, researchers have improvised the existing in-pipe inspection robots by developing hybrid locomotion by combining two or more propulsion mechanism in achieving robust but yet flexible robot platform. In this paper, several hybrid robots have been reviewed and categorized according to their implemented locomotion system. The hybrid locomotion systems are caterpillar wall-pressed type, wheeled wall-pressed type and wheeled wall-pressing screw type. Each hybrid locomotion system is developed according to distinct design requirements for specific environment and might be not suitable for other application. The aim of this review is to highlight the current innovation of in-pipe robot for inspection. Based on the study, wall pressed type is the most popular main locomotion system in in-pipe robot development. Most of the prototypes are able to travel into branches with the same diameter as the pipe. Integration of caterpillar wheel gives more advantage in preventing motion singularity problem while surpassing branches. On the other hand, wheeled wall-pressed type provides advantage in high speed mobility. Wheeled wall pressing screw type gives the best navigation in curved pipe. None of these inventions show their ability in navigating bigger pipe to smaller branches. 2012 The Authors.